IL1β Promotes TMPRSS2 Expression and SARS-CoV-2 Cell Entry Through the p38 MAPK-GATA2 Axis - Cioccarelli, Chiara; Sánchez-Rodríguez, Ricardo; Angioni, Roberta; Venegas, Francisca C.; Bertoldi, Nicole; Munari, Fabio; Cattelan, Annamaria; Molon, Barbara; Viola, Antonella (Frontiers in Immunology, 2021)
After the outburst of the SARS-CoV-2 pandemic, a worldwide research effort has led to the uncovering of many aspects of the COVID-19, among which we can count the outstanding role played by inflammatory cytokine milieu in the disease progression. Despite that, molecular mechanisms that regulate SARS-CoV-2 pathogenesis are still almost unidentified. In this study, we investigated whether the pro-inflammatory milieu of the host affects the susceptibility of SARS-CoV-2 infection by modulating ACE2 and TMPRSS2 expression. Our results indicated that the host inflammatory milieu favors SARS-CoV-2 infection by directly increasing TMPRSS2 expression. We unveiled the molecular mechanism that regulates this process and that can be therapeutically advantageously targeted.